Lung Adenocarcinoma Invasiveness Risk in Pure Ground-Glass Opacity Lung Nodules Smaller than 2 cm - Lee, Geun Dong; Park, Chul Hwan; Park, Heae Surng; Byun, Min Kwang; Lee, Ik Jae; Kim, Tae Hoon; Lee, Sungsoo (The Thoracic and Cardiovascular Surgeon, 2019)
Background We aimed to identify clinicopathologic characteristics and risk of invasiveness of lung adenocarcinoma in surgically resected pure ground-glass opacity lung nodules (GGNs) smaller than 2 cm.Methods Among 755 operations for lung cancer or tumors suspicious for lung cancer performed from 2012 to 2016, we retrospectively analyzed 44 surgically resected pure GGNs smaller than 2 cm in diameter on computed tomography (CT).Results The study group was composed of 36 patients including 11 men and 25 women with a median age of 59.5 years (range, 34–77). Median follow-up duration of pure GGNs was 6 months (range, 0–63). Median maximum diameter of pure GGNs was 8.5 mm (range, 4–19). Pure GGNs were resected by wedge resection, segmentectomy, or lobectomy in 27 (61.4%), 10 (22.7%), and 7 (15.9%) cases, respectively. Pathologic diagnosis was atypical adenomatous hyperplasia, adenocarcinoma in situ, minimally invasive adenocarcinoma (MIA), or invasive adenocarcinoma (IA) in 1 (2.3%), 18 (40.9%), 15 (34.1%), and 10 (22.7%) cases, respectively. The optimal cutoff value for CT-maximal diameter to predict MIA or IA was 9.1 mm. In multivariate analyses, maximal CT-maximal diameter of GGNs ≥10 mm (odds ratio, 24.050; 95% confidence interval, 2.6–221.908; p = 0.005) emerged as significant independent predictor for either MIA or IA. Estimated risks of MIA or IA were 37.2, 59.3, 78.2, and 89.8% at maximal GGN diameters of 5, 10, 15, and 20 mm, respectively.Conclusion Pure GGNs were highly associated with lung adenocarcinoma in surgically resected cases, while estimated risk of GGNs invasiveness gradually increased as maximal diameter increased.
Keywords: lung cancer; adenocarcinoma; ground-glass opacity lung nodules; histopathology